Effects of Feeding a Finishing Diet Blended with Different Phases of Nursery Diets on Growth Performance and Economics of Nursery Pigs - F. Wu; K. Coble; C. Hastad; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 1,260 weaned pigs (PIC TR4 × (Fast LW × PIC L02); initially 12.9 lb BW)) were housed in a commercial research barn and used in a 47-d study to determine the effects of blending a finishing diet into different phases of nursery diets on pig growth performance. Pens of pigs were blocked by initial BW and gender and allotted to 1 of 4 treatment groups (15 pens/treatment). In a 5-phase feeding program, the 4 treatments were: 1) standard nursery diets throughout (control); or standard nursery diets with 5.5 lb/pig of late finishing feed blended at the beginning of 2) Phase 2; 3) Phase 3; or 4) Phase 4. Phase changes were based on feed budgets. From d 0 to 7, all pigs received the same standard Phase 1 diet and had similar growth performance. Compared with pigs from control, blending finishing feed into the Phase 2 period resulted in poorer (P<0.01) ADG, ADFI, and F/G from d 7 to 14, poorer (P = 0.025) F/G from d 21 to 28, decreased (P = 0.028) ADG from d 28 to 35, and decreased (P<0.05) ADFI and F/G from d 35 to 47. Blending finishing feed during Phase 3 resulted in worsened (P<0.001) ADG and F/G from d 14 to 21, decreased (P = 0.010) ADG from d 21 to 28, and lower (P<0.05) ADFI and F/G from d 35 to 47 compared with control pigs. Pigs that received blended diet in Phase 4 had impaired (P<0.001) ADG and F/G from d 21 to 28, but had improved (P = 0.010) F/G from d 35 to 47. Overall (d 0 to 47), blending the finishing diet into Phase 2 decreased (P<0.05) ADG, ADFI, and final BW, but did not affect F/G compared with control pigs or pigs that had finishing feed blended into the Phase 4. Blending finishing feed into Phase 3 or 4 did not influence overall growth performance. Pigs that had finishing feed blended into Phase 2 or 3 had lower (P<0.05) overall feed costs than pigs from control and Phase 4 blending treatments. Gain value was decreased (P<0.05) when finishing feed was blended into Phase 2 compared with the control or when feed was blending into Phase 4. However, no differences in feed cost per lb of gain and only numerical differences in income over feed cost were observed among the treatments. In conclusion, feeding finishing feed in early nursery phase negatively affected pig growth performance; however, blending approximately 5.5 lb/pig finishing feed into nursery diets for pigs greater than 22 lb BW did not affect overall growth performance.
Keywords: blending; finishing feed; nursery feed; growth; nursery pig